Historical and theoretical legal aspect of children's Ombudsman activity in the Republic of Kazakhstan as a guarantor of minor`s rights and freedoms realization - Abikenova, G.B. (Bulletin of the Karaganda University “Law Series”, 2018)
Protection of the child’s rights is among the most actual of modern social problems generated by the violation of the rights of this category of the population in recent years and the lack of effective mechanisms for protection and restoration of violated rights of minors, imperfection of legislation in this area. Meanwhile, the UN Convention on the rights of the child which is the primary international document regulating the rights of the child stipulates the state's obligation to provide the child the protection necessary for his prosperity and to take all appropriate legislative and administrative measures. One of the most effective guarantors of minor’s constitutional rights and freedoms realization in the Republic of Kazakhstan is the Institute of the children's rights Ombudsman. The article analyzes the powers and the basic directions of activity of the children's rights Ombudsman Institute in the Republic of Kazakhstan, the historical aspects of formation and development, as well as issues of functioning and improvement of this Institute. A review of the national legislation in the sphere of implementation of the rights and freedoms of minors was carried out. The work states that Institute of Child`s Ombudsman, from the very beginning of its existence, has proved effectiveness in respect of the legitimate rights and freedoms of minors realization, its demand for the society and the authorities. The recommendations are proposed.